Simulation of aggregate behavior in low confinement geotechnical applications. (September 2020) - Mashayekhi, Meysam; Kaliakin, Victor N.; Meehan, Christopher L.; Adams, Michael T.; Nicks, Jennifer E.
Abstract: Isotropic compression and drained axisymmetric triaxial compression tests were performed on six structural backfill aggregates commonly used in the construction of geosynthetic-reinforced soil (GRS) systems to characterize their shear behavior. The behavior of these aggregates was then simulated using the Single Hardening Model (SHM) for frictional materials. The confining pressures that were tested and analyzed in the current study (e.g., 34 to 413 kPa) are generally consistent with those encountered with various GRS applications. The pressures at the bottom end of this range are relatively low for typical geotechnical engineering testing and simulation approaches. Certain modifications to the SHM were required in order to more accurately simulate the volume change response that occurs under drained loading conditions at these lower confining pressures. The model simulation results showed good agreement with the results from the triaxial compression tests. These findings are important, as accurately simulating the volumetric response during shear is very important for GRS systems because, although initially compacted, such systems are subjected to relatively low confining pressures during service conditions.